Tunisian Validation of The Children’s Depression Inventory-2 in School-based Children - Ayadi, Hela; Boudabous, Jaweher; Kerkeni, Ali; Kraiem, Mayssa; Yaich, Sourour; Moalla, Yousr (Current Psychiatry Research and Reviews, 2025)
BackgroundClinical observations advocate for increasingly depressive disorders in children in Tunisia. However, no studies evaluating the prevalence of depression in Tunisian children have been published because of the lack of validated Arabic depression scale for children.AimThus, we aimed to validate the Children’s Depression Inventory in its second edition (CDI-2).MethodsThe present study was conducted on a representative sample of school-based Tunisian children in the city of Sfax. The sample was composed of 500 children aged 8– 12 years. The study took place in two phases. The first phase consisted of testing scales for participating children. During the second phase, children with depressive symptoms, according to the CDI-2, were invited for psychiatric interviews. Statistical evaluation included an assessment of the CDI-2 internal consistency, test-retest reliability and concurrent validity. Multi-trait scaling analysis was used to examine item convergent and discriminant validity. The CDI-2 was reliable in terms of internal consistency (0.887), with item-total score correlations ranging from 0.311 to 0.674. All items exceeded the 0.4 criterion for convergent validity in all subscales.ResultsThe mean total score of the CDI-2 for the whole sample was 12.59 (SD=9.28). CDI-2 and DSRS-C scores correlated 0.775. Correlations between DSRS-C scores and CDI-2 subscales ranged from 0.66 to 0.783.ConclusionWe concluded that the CDI-2 Arabic version has satisfactory psychometric properties and is reliable for use in the Tunisian pediatric population.
Keywords: reliability